2018
DOI: 10.3892/ijo.2018.4610
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-98-5p inhibits proliferation and metastasis in non-small cell lung cancer by targeting TGFBR1

Abstract: MicroRNAs (miRNAs or miRs) have recently emerged as key regulators of various types of cancer, including non-small cell lung cancer (NSCLC). The disrupted expression of miRNAs is associated with tumorigenesis and metastasis; however, the underlying mechanisms remain unclear. In this study, we demonstrate that miR-98-5p is downregulated in NSCLC and that miR-98-5p deficiency is associated with an advanced clinical stage and metastasis. A dual-luciferase reporter assay was performed to confirm that transforming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 40 publications
2
32
0
2
Order By: Relevance
“…Recent published reports also shows that TGF-beta1 appear to be overproduced in COVID-19 patients [69]. Hsa-miR-9-5p, hsa-miR-98-5p and hsa-miR-23b-3p regulate TGFBR receptors during pulmonary disorders [68,70,71]. These miRNAs are part of the regulatory circuit identified in the present study and are antiviral host-miRNAs which can potentially target SARS-CoV-2 genes [10].…”
Section: Discussionsupporting
confidence: 70%
“…Recent published reports also shows that TGF-beta1 appear to be overproduced in COVID-19 patients [69]. Hsa-miR-9-5p, hsa-miR-98-5p and hsa-miR-23b-3p regulate TGFBR receptors during pulmonary disorders [68,70,71]. These miRNAs are part of the regulatory circuit identified in the present study and are antiviral host-miRNAs which can potentially target SARS-CoV-2 genes [10].…”
Section: Discussionsupporting
confidence: 70%
“…Increasing evidence has demonstrated that numerous miRNAs are dysregulated in NScLc and that this dysregulation is a hallmark of NScLc (30)(31)(32). Recently, miRNAs have been identified as a novel player in gene regulation in NSCLC, with aberrant miRNAs expression serving pivotal roles in formation and progression of NScLc (33)(34)(35). A detailed investigation of cancer-associated miRNAs in NScLc is therefore crucial for identifying effective therapeutic targets for this disease.…”
Section: Discussionmentioning
confidence: 99%
“…According to Wang et al, miR‐133a may suppress cell invasion by targeting TGFBR1 in NSCLC . Jiang et al hold the view that miR‐98‐5p inhibited proliferation and metastasis of NSCLC by targeting TGFBR1 . Recent research has suggested that TGFBR1 was activated after myocardial infarction in rats and was associated with the degree of remodeling, suggesting that TGFBR1 may be a candidate prognostic biomarker on cardiomyocyte.…”
Section: Discussionmentioning
confidence: 99%
“…25 Jiang et al hold the view that miR-98-5p inhibited proliferation and metastasis of NSCLC by targeting TGFBR1. 26 Recent research has suggested that TGFBR1 was activated after myocardial infarction in rats and was associated with the degree of remodeling, 27 suggesting that TGFBR1 may be a candidate prognostic biomarker on cardiomyocyte. Consistent with previous reports, our findings revealed that TGFBR1 was highly expressed in H/R model, and its change was decreased/increased after miR-27 mimic/inhibitor treatment.…”
Section: Downregulated Expression Of Mir-27 In Myocardial Ischemiamentioning
confidence: 99%